Epitype-inducing temperatures drive DNA methylation changes during somatic embryogenesis in the long-lived gymnosperm Norway spruce - Viejo, Marcos; Tengs, Torstein; Yakovlev, Igor; Cross, Hugh; Krokene, Paal; Olsen, Jorunn E.; Fossdal, Carl Gunnar (Frontiers in Plant Science, 2023)
An epigenetic memory of the temperature sum experienced during embryogenesis is part of the climatic adaptation strategy of the long-lived gymnosperm Norway spruce. This memory has a lasting effect on the timing of bud phenology and frost tolerance in the resulting epitype trees. The epigenetic memory is well characterized phenotypically and at the transcriptome level, but to what extent DNA methylation changes are involved have not previously been determined. To address this, we analyzed somatic epitype embryos of Norway spruce clones produced at contrasting epitypeinducing conditions (18 and 28 °C). We screened for differential DNA methylation in 2744 genes related mainly to the epigenetic machinery, circadian clock, and phenology. Of these genes, 68% displayed differential DNA methylation patterns between contrasting epitype embryos in at least one methylation context (CpG, CHG, CHH). Several genes related to the epigenetic machinery (e.g., DNA methyltransferases, ARGONAUTE) and the control of bud phenology (FTL genes) were differentially methylated. This indicates that the epitype-inducing temperature conditions induce an epigenetic memory involving specific DNA methylation changes in Norway spruce.